Sharply contoured theta waves are the human correlate of ponto-geniculo-occipital waves in the primary visual cortex. Issue 8 (August 2018) - Frauscher, Birgit; Joshi, Sweta; von Ellenrieder, Nicolas; Nguyen, Dang Khoa; Dubeau, François; Gotman, Jean
Highlights: We investigate the presence of ponto-geniculo-occipital (PGO) waves in the human primary visual cortex using stereo-EEG. We found sharply contoured theta waves in the visual cortex during phasic versus tonic REM sleep. This work suggests that sharply contoured theta waves are the human correlate of PGO waves. Abstract: Objective: Ponto-geniculo-occipital (PGO) waves occurring along the visual axis are one of the hallmarks of REM sleep in experimental animals. In humans, direct evidence is scarce. There is no systematic study of PGO waves in the primary visual cortex. Methods: Eleven epilepsy patients undergoing combined intracranial EEG/polysomnography had 71 channels recording physiological EEG activity from various cortical areas; seven channels recorded from the primary visual cortex. An equal number of 4-s phasic and tonic REM segments were selected. Patterns consistent with PGO waves were visually analyzed in both states in the primary visual cortex. Spectral analysis compared activity in the primary visual cortex with the remaining cortical areas. Results: Visual inspection revealed an increase in sharply contoured theta waves (duration: 150–250 ms) in the primary visual cortex during phasic as compared to tonic REM sleep. Spectral analysis confirmed a 32% increase in mean absolute theta power during phasic versus tonic REM sleep (p corrected = 0.014). Conclusion: No classical PGO waves, but sharply contoured theta waves were found in the human primary visual cortex during phasic as opposed to tonic REM sleep. Significance: This research suggests that sharply contoured theta waves are the human correlate of PGO waves described in experimental animal models.